2022
DOI: 10.3390/ma15010334
|View full text |Cite
|
Sign up to set email alerts
|

Defect Passivation and Carrier Reduction Mechanisms in Hydrogen-Doped In-Ga-Zn-O (IGZO:H) Films upon Low-Temperature Annealing for Flexible Device Applications

Abstract: Low-temperature activation of oxide semiconductor materials such as In-Ga-Zn-O (IGZO) is a key approach for their utilization in flexible devices. We previously reported that the activation temperature can be reduced to 150 °C by hydrogen-doped IGZO (IGZO:H), demonstrating a strong potential of this approach. In this paper, we investigated the mechanism for reducing the activation temperature of the IGZO:H films. In situ Hall measurements revealed that oxygen diffusion from annealing ambient into the conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The metal cations become very active, causing disruption of the equilibrium microstructure of the initial amorphous oxides. Velichko et al reported that the introduction of H enabled the low-temperature fabrication of IGZO TFTs by reducing the barrier for oxygen diffusion, which is similar to our explanation of increasing the activity of metal cations. Subsequently, the microstructure undergoes a rearrangement, resulting in a new configuration characterized by a strengthened M–O network and fewer defects.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The metal cations become very active, causing disruption of the equilibrium microstructure of the initial amorphous oxides. Velichko et al reported that the introduction of H enabled the low-temperature fabrication of IGZO TFTs by reducing the barrier for oxygen diffusion, which is similar to our explanation of increasing the activity of metal cations. Subsequently, the microstructure undergoes a rearrangement, resulting in a new configuration characterized by a strengthened M–O network and fewer defects.…”
Section: Resultssupporting
confidence: 87%
“…44 Thus, numerous metal−hydrogen bonds (M−H) 45 form as evidenced by the optical absorption observation of additional H-related defects (such as H-DX − and H i − ). The bond dissociation energy required to break M−H bonds is approximately 1/3−2/3 of that needed for M−O bonds, 46 as detailed in Table S2. Therefore, a significant number of M−H bonds break before the obvious desorption of oxygen in the initial stage of the annealing process.…”
Section: Resultsmentioning
confidence: 99%
“…The supercell was obtained by setting lattice vectors to (420), (040), and (221) for the IGZO crystal and reducing the lattice constant c to one-third [ 29 ]. To have an insight into the capture process of the CAAC-IGZO FETs with Al 2 O 3 dielectric, a variety of different intrinsic defects are considered, which may widely exist and have been suggested as the cause of reliability issues [ 30 , 31 , 32 , 33 , 34 , 35 ] in oxide semiconductor materials, for instance, oxygen vacancy (V O ), oxygen interstitial (O i ), hydrogen interstitial (H i ), hydrogen substituted oxygen (H O ) and hydroxyl interstitial ((OH) i ), and so on. Here, the defect of Ho can be regarded as a coexistence of H i and V O .…”
Section: Computation Methodologymentioning
confidence: 99%
“…In general, the SS value of a TFT is strongly affected by defects near the semiconductor Fermi level [ 2 , 12 ]. We recently reported from hard X-ray photoelectron spectroscopy analysis that intentionally introduced hydrogen is effective in reducing defects near the Fermi level in amorphous IGZO [ 40 , 41 , 42 , 43 , 44 ]. The SS values of the In 2 O 3 :H TFTs, shown in Figure 2 d, increased at a T ann of 400 °C and higher, indicating defect creation.…”
Section: Resultsmentioning
confidence: 99%